The Effectiveness of Using Interactive Multimedia with Local Purworejo Culture on Learning Outcomes of Class V Elementary School Students - Pangestika, Rintis Rizkia; Yansaputra, Galih; Setyanto, Setyanto (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
This aim is to determine the effectiveness of the use of interactive multimedia of the local culture of Purworejo on the learning outcomes of fifth-grade elementary school students. This type of research in this research is descriptive quantitative research. The target of this research is the fifth-grade elementary school students with a total of 22 students. This research design using One-Shot Case Study. This study uses data collection techniques with the written test method. The test given is in the form of an essay question. The effectiveness of this study was obtained based on the number of students who obtained a completeness score of â‰¥ 70 as much as 75% of the total number of students. The results showed that the scores obtained by students who achieved the minimum completeness criteria were 19 students or 86.36% and those who obtained scores below the completeness criteria were 3 students or 13.64%. The average score was 80.2. Thus, it can be said that the use of interactive multimedia is effective on student learning outcomes.